Analisis dan Perancangan Aplikasi Sistem Informasi Akuntansi Penjualan dan Pembelian Menggunakan Microsoft Access 2019 (Studi Kasus Pada PD Makmur – Bandung) - Siti Nuranisa; Darya Setia Nugraha; Iyeh Supriatna; Rina Nurmalina; Jouzar Farouq Ishak (Jurusan Akuntansi Politeknik Negeri Bandung, 2023)
PD Makmur is a company that manufactures and sells industrial brushes. Recording of sales and purchases is still done manually and does not have employees who specifically handle sales and purchases so that owners often do not record sales and purchases due to time constraints. In addition, there is no report on sales and purchases per certain period so that problems arise, namely the owner does not accurately know the total sales and purchases in a certain period. Owners also have difficulty making decisions regarding sales and purchases. This study aims to design a computerized sales and purchase accounting information system application program using Microsoft Access 2019 which is expected to be able to handle related problems. The method used in this study is a qualitative descriptive method with a case study and development approach and uses the SDLC (System Development Life Cycle) method as an analytical tool. In addition, the authors also conducted observations, interviews, and documentation to collect the required data. By designing this application, the results obtained are that it is easier for companies to keep records, and make sales reports, purchase reports, production reports and inventory reports.